Country furniture - Watson, Aldren Auld, 1917- (New York: Crowell, 1974)
Describes the history, community, and daily life of the early American furniture maker, the types of wood he chose, his shop, tools, techniques, and business affairs.
Bibliography: p. 265-267.
Keywords: Furniture industry and trade -- New England -- History; Furniture making; Furniture -- New England; Furniture making; Furniture -- New England